Cross-border divorce law : Brussels II bis - Ni Shuilleabhain, Maire (Maire Treasa) (Oxford : Oxford University Press, 2010)
'This book examines the divorce aspects of the Brussels II bis Regulation (Regulation 2201/2003). It gives detailed consideration to the new jurisdictional rules and to the likely interpretation of the core jurisdictional concept of'habitual residence'. The scope of the Regulation is analyzed, and particular attention is given to its possible application to civil partnerships and same-sex marriages. The book also analyzes the Regulation's impact on ancillary relief matters and its interaction with related measures of Community and national law in that context. The new recognition procedures are considered in detail, as are the defences to recognition, and the wider consequences of automatic recognition are assessed. The book provides in-depth coverage of relevant case-law of the national and Community courts, and particular attention is given to the likely impact of the cases decided under the 1968 Brussels Convention and under Regulation 44/2001 (including the Owusu case)'--
Background, context, and principles of interpretation -- Habitual residence, domicile and other connecting factors -- Personal, temporal, material and geographic scope of Brussels II bis -- Jurisdictional bases under Brussels II bis -- Declining jurisdiction under Brussels II bis -- Recognition of judgments under Brussels II bis -- Final observations.
Includes bibliographical references (p. [287]-301) and index.
Keywords: Divorce -- Law and legislation -- European Union countries; Conflict of laws -- Divorce -- European Union countries; Jurisdiction -- European Union countries